Corrosion Protection Coatings from Size-Specified Graphene Oxide - Nurul Huda, Abu Bakar; Jamil, Ismail; K. F., Chong (2020)
Corrosion performance of graphene oxide (GO) coatings from different sheets sizes in 3.5 wt% NaCl solution was investigated. The GO dispersion was subjected to 5 and 10 hours of ultrasonication before electrophoretically deposited (EPD) onto the copper substrate. It was found that the EPD-GO coating from smaller sheets (10h ultrasonication) possess hydrophobic, thinner film and smooth surfaces. It is suggested that the corrosion performance of the coating from smaller GO sheets is improved due to the surface texture and compactness of the coating as compared to the larger GO sheets.